Callus cell, shoot and stem proliferation data from pineapple crown and banana inflorescence in vitro: Biochemical and antioxidant properties - Hossain, A.S.; Uddin, M.M. (Elsevier, 2017)
The data article contains the experimental data and images on the callus cell, shoot and stem proliferation from pineapple crown slice and banana inflorescence in vitro. Investigated data are related to the research article “Effects of benzylaminopurine and naphthalene acetic acid on proliferation and shoot growth of pineapple (Ananas comosus L. Merr) in vitro” Alsaif et al. (2011) [1] and “Plantlet Production through Development of Competent Multiple Meristem Cultures from Male Inflorescence of Banana, Musa acuminta cv. ׳Pisang Mas׳(AA)” Wirakarnain et al. (2008) [2]. In the experimental data 1, physiological, (shoot weight, number length and stem proliferation) biochemical (total sugar and chlorophyll) and nutritional ((K+ and NO3−) data using BAP, MS medium and NAA growth regulators in pineapple have been explored. In the experimental data 2, physiological, (callus weight, shoot number and length) biochemical (total sugar, chlorophyll, total phenol, DPPH) and nutritional (K+ and NO3−) data employing BAP +IAA, MS medium and NAA growth regulators in banana have been exhibited. Overall quantitative measurement was observed by Spectrophotometer. In the experimental data, BAP was shown the best effective hormone for the both pineapple and banana explants regeneration.